Empowering School-Dropout Youth Through Woodcraft Education: A Case Study Of Program Implementation In A Community Learning Center - Shella Monica; Melly Susanti (CITACONOMIA : Economic and Business Studies, 2026)
School dropout remains a persistent challenge that limits young people's educational and employment opportunities. This study examined the implementation of a woodcraft education program as an empowerment strategy for school-dropout youth at PKBM Insan Kreatif, Indonesia. Using a qualitative descriptive case study design, the study involved 15 school-dropout youth aged 15–21 years. Data were collected through semi-structured interviews with the program manager and tutors, observations, and document analysis, and were analyzed using thematic analysis. The findings revealed that the program was implemented through collaboration with a local furniture enterprise, providing participants with hands-on training in wood identification, machine operation, cutting, shaping, sanding, varnishing, and painting. The program not only enhanced vocational skills but also fostered self-confidence, discipline, responsibility, and active engagement. This study contributes to the literature by exploring the implementation of a community-based woodcraft education program among school-dropout youth, a population that remains underexplored in vocational education research. The findings highlight the potential of non-formal vocational education to support youth empowerment and social inclusion.